Digital customer success why the next frontier of CS is digital and how you can leverage it to drive durable growth - Mehta, Nick 1977-; Capote, Kellie (Ascent Audio, 2024)
Automate your customer success efforts to reduce churn and increase profits. In Digital Customer Success: The Next Frontier, a team of trailblazing customer success professionals and digital entrepreneurs delivers an insightful discussion of the next stage in customer success management. In the book, you'll discover how to design and deploy touchless and automated digital interventions that help your software users learn and grow as they use your product and unlock the value trapped within it-without ever needing to reach out to a live customer success manager. The authors provide a detailed "How-To" guide to Digital customer success that explains how you can meet the needs of your customers, investors, and team members. You'll explore the basics of the authors' original Digital Customer Success Maturity Model and the core tenets of how to get started. After that, you'll find: explanations of the ideal organizational structures to enable digital customer success management; case studies and examples from real companies blazing new trails in customer success; and critical success measurements and metrics you can use to determine if your company is on the right track or if it needs to reorient.